Obama's Guantánamo : Stories from an Enduring Prison - Hafetz, Jonathan (Book collections on Project MUSE., 2016)
"Obama's Guantánamo: Stories from an Enduring Prison describes President Obama's failure to close America's enduring offshore detention center, as he had promised to do within his first year in office, and the costs of that failure for those imprisoned there. Like its predecessor, Guantánamo Lawyers: Inside a Prison Outside the Law, Obama's Guantánamo consists of accounts from lawyers who have not only represented detainees, but also served as their main connection to the outside world. Their stories provide us with an accessible explanation of the forces at work in the detentions and place detainees' stories in the larger context of America's submission to fearmongering. These stories demonstrate all that is wrong with the prison and the importance of maintaining a commitment to human rights even in times of insecurity"--Publisher's web site.